1. Zapisz w prostszej postaci:
a) 7x² − 4x − 6x² + 4 − x² + 5x = . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
b) −2(3a − 2b) − 4a(2 − 3a + 2b) = . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
c) (4 − x)(2x + 5) − 4 = . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
d) (4 − 2x)(3x − 3) − 2x(3x + 1) = . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-06T16:13:33+01:00
A) 7x² − 4x − 6x² + 4 − x² + 5x = x+4

b) −2(3a − 2b) − 4a(2 − 3a + 2b) = -6a+4b-8a+12a²-8ab = 12a²+-14a-8ab+4b

c) (4 − x)(2x + 5) − 4 = 8x+20-2x²-5x-4 = -2x²+3x+16

d) (4 − 2x)(3x − 3) − 2x(3x + 1) = 12x-12-6x²+6x-6x²-2x = -12x²+16x-12